2003
DOI: 10.1097/00005131-200301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Triangular Osteosynthesis and Iliosacral Screw Fixation for Unstable Sacral Fractures: A Cadaveric and Biomechanical Evaluation Under Cyclic Loads

Abstract: Triangular osteosynthesis for unstable transforaminal sacral fractures provides significantly greater stability than iliosacral screw fixation under in vitro cyclic loading conditions. In vitro cyclic loading, as a limited simulation of early stages of patient mobilization in the postoperative period, allows for a time-dependent evaluation of any fracture fixation system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
151
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(163 citation statements)
references
References 44 publications
2
151
0
10
Order By: Relevance
“…PTO combines a vertical (lumbopelvic) and horizontal (iliosacral) fixation, providing a good degree of protection against cranial migration of the injuried half of the pelvic ring [15] by transferring vertical loads from the lower lumbar spine to the ilium. The sacral fracture result partially protected from these loads and the horizontal component stabilizes the fracture in the horizontal plane, so resisting certain counterforces, such as the internal rotation observed in a biomechanical study [17]. The PTO for unstable sacral fractures provides greater immediate post-operative stability compared with iliosacral screw fixation, as shown in an experimental study [17].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…PTO combines a vertical (lumbopelvic) and horizontal (iliosacral) fixation, providing a good degree of protection against cranial migration of the injuried half of the pelvic ring [15] by transferring vertical loads from the lower lumbar spine to the ilium. The sacral fracture result partially protected from these loads and the horizontal component stabilizes the fracture in the horizontal plane, so resisting certain counterforces, such as the internal rotation observed in a biomechanical study [17]. The PTO for unstable sacral fractures provides greater immediate post-operative stability compared with iliosacral screw fixation, as shown in an experimental study [17].…”
Section: Discussionmentioning
confidence: 95%
“…The sacral fracture result partially protected from these loads and the horizontal component stabilizes the fracture in the horizontal plane, so resisting certain counterforces, such as the internal rotation observed in a biomechanical study [17]. The PTO for unstable sacral fractures provides greater immediate post-operative stability compared with iliosacral screw fixation, as shown in an experimental study [17].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, Schildhauer et al [12] pointed out that this kind fixation cannot guarantee rotational stability because it addresses vertical forces only, whereas rotational stability cannot be achieved by the vertical twopoint fixation. To solve this problem, triangular osteosynthesis for unstable sacral fractures had been recently introduced [12][13][14][15][16]. This fixation combines a transverse fixation with a lumbopelvic distraction osteosynthesis, providing clinically and biomechanically sufficient multiplanar stability [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these fixation instruments can resist vertical shear forces, provide unrestricted weightbearing, and secure mobilization after operation. Recent studies demonstrated that triangular osteosynthesis is a new option for the treatment of type C pelvic fracture following unstable sacral fractures [12][13][14][15][16]. This fixation combines a lumbopelvic distraction osteosynthesis and a transverse fixation, which provides multiplanar stability.…”
Section: Introductionmentioning
confidence: 99%